How to grow Upland rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Arraudeau, M.A., and B.S.Vergara, 1988. 'A Farmer's Primer on Growing Upland Rice' 280pp. ISBN 971 104 170 7.